Hubungan Pengetahuan Dan Sikap Mahasiswa Program Studi Tata Boga Universitas Negeri Jakarta Dengan Tindakan Penggunaan Plastik Untuk Minuman Panas - Lulu Amalia Octaviany; Efrina; Alsuhendra (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
Plastics are organic materials formed into various shapes when exposed to heat and pressure. Plastics have weaknesses and are dangerous for the materials they pack, namely the possibility of migration or transfer of monomer substances from plastic materials into food and beverages. The aims of this research is to analyze the relationship between knowledge and attitudes of student’s to measure the use of plastic for hot drinks. This type of this research is survey with cross-sectional approach. The samples in this study are students of the Culinary Education Study Program at the Jakarta State University, with a total sample of 66 respondents using the disproportionate stratified random sampling technique. Data has been analyzed using descriptive analysis and inferential analysis. The results of this research show that the percentage of 66 students who have high knowledge about plastics is 54,5%, 95,5% of students have high attitudes in using plastic, and 78,8% of students have high action in using plastic. Meanwhile, the correlation test results showed a positive relationship between student's knowledge and attitudes with the use of plastic (r_count = 0.765 > r_table = 0.244) with a determination coefficient of 58,5%. Based on the research results, it is expected that Culinary Education students will maintain their attitudes and actions in using plastic to avoid the dangers inflicted by plastic.